2023
DOI: 10.1016/j.gocm.2022.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Urban-rural differences in the pregnancy-related adverse outcome

Abstract: BackgroundLittle is known about potential urban-rural differences in adverse pregnancy outcomes. The purpose of this study is to look into the urban-rural differences in the trend of adverse maternal and neonatal outcomes.MethodsWe retrospectively assessed the pregnancy outcome of singleton pregnant mothers who gave birth at a tertiary hospital in Bandar Abbas, Iran, between January 1st, 2020, and January 1st, 2022. Mothers were divided into two groups based on living residency: 1) urban groupand 2) rural grou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Among other demographic variables, living residency was linked to iron-deficiency anemia. Iron-deficiency anemic women mostly lived in rural areas, consistent with previous studies [13,14].…”
Section: Discussionsupporting
confidence: 90%
“…Among other demographic variables, living residency was linked to iron-deficiency anemia. Iron-deficiency anemic women mostly lived in rural areas, consistent with previous studies [13,14].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, a research endeavor sought to assess variances between urban and rural areas concerning adverse outcomes related to pregnancy. The ndings revealed that mothers residing in rural areas faced a greater likelihood of anemia, with an adjusted odds ratio of 2.02 (95% CI: 1.07-2.34), compared to their urban counterparts [31]. However, another study conducted in Ethiopia indicated that there was no variation in the prevalence of anemia between pregnant women residing in rural and urban areas [32].…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, a research endeavor sought to assess variances between urban and rural areas concerning adverse outcomes related to pregnancy. The ndings revealed that mothers residing in rural areas faced a greater likelihood of anemia, with an adjusted odds ratio of 2.02 (95% CI: 1.07-2.34), compared to their urban counterparts [32]. However, another study conducted in Ethiopia indicated that there was no variation in the prevalence of anemia between pregnant women residing in rural and urban areas [33].…”
Section: Discussionmentioning
confidence: 95%